2017
DOI: 10.1080/10826084.2017.1400068
|View full text |Cite
|
Sign up to set email alerts
|

From Narcotic to Normalizer: The Misperception of Methadone Treatment and the Persistence of Prejudice and Bias

Abstract: This article concentrates on methadone maintenance as a normalizer for the impairments of opioid addiction, and the misunderstandings of it as a substitute for heroin that continues an opiate addiction. Methadone treatment was developed by Drs. Dole, Nyswander, and Kreek. Their cutting-edge theory transformed the way that opioid addiction is perceived and their work changed methadone from a narcotic to withdraw addicts to a medication that is a maintenance normalizer for a chronic condition. Their extensive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The misconception that opioid addiction is a choice increases the likelihood of social rejection and the risk of relapse of MAT patients. 10 The fact that this study indicated that a 24-hour educational process could be instrumental in challenging and transforming attitudes toward those with opioid addiction has important implications for addiction medicine training.…”
Section: Discussionmentioning
confidence: 91%
“…The misconception that opioid addiction is a choice increases the likelihood of social rejection and the risk of relapse of MAT patients. 10 The fact that this study indicated that a 24-hour educational process could be instrumental in challenging and transforming attitudes toward those with opioid addiction has important implications for addiction medicine training.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding physical impairment, methadone maintenance patients showed greater di culty and impaired psychomotor skills in compared with buprenorphine [9]. However, it is important to stress that methadone remains as a safe pro le for its use in opiate-addicted patients [7,42].…”
Section: Discussionmentioning
confidence: 99%
“…Methadone is extensively studied and is an effective treatment for OUD [ 34 ]. One benefit identified from the patient’s perspective is that the individual might soon return to their typical daily routine, shortly after initiation of methadone treatment [ 35 ]. Previous studies explored various barriers to methadone adherence, concluding that one of the main impediments for patients is attending the clinic daily to receive treatment [ 36 , 37 ] In contrast, one of the main benefits of buprenorphine and buprenorphine/naloxone treatment is that the individual can take the treatment at home.…”
Section: The Vicious Cycle Of Opioid Use Disorder In the Plwha Popmentioning
confidence: 99%